Habitação coletiva na área central de São Paulo: políticas urbanas e o concurso "Habita Sampa 2004" - Simões, Paulo Duarte (2010)
This work presents Morar no Centro program, focusing social habitation promotion in São Paulo s downtown area, in public municipal administration since 2001 until 2004. It approaches architectures competition importance, like proposal divulgation form of this nature habitation case, to encourage different proposals related to an inclusion social policy. It also analyzes the three best placed architectural projects on the competition Habita Sampa 2004, proposed to "Conjunto Assembléia", deciding about how that solutions attend to several asks and architectural project determinants, that this competition and habitation politics expect.